The European Network of Gynecological Oncological Trial Groups. (January 2012) - Vergote, I; Pujade-Lauraine, E; Pignata, S; Kristensen, GB; Ledermann, J; Casado, A; Sehouli, J; Mirza, M; Fossati, R; Marth, C; Ottevanger, N; Del Campo, J; et al.
The European Network of Gynecological Oncological Trial Groups (ENGOT) is a research network of 17 European academic gynecological cancer trial groups. ENGOT coordinates and promotes clinical trials within Europe in patients with gynecological cancer. In 2010 ENGOT published the requirements for trials between the academic ENGOT and pharmaceutical companies. This has led to a number of new ENGOT trials performed in collaboration with the industry and better coordination of gynecological cancer trials in Europe. Further goals for ENGOT are to increase translational research in ENGOT trials and to develop more trials in cervical cancer, endometrial cancer and in rare gynecological cancers.